2019
DOI: 10.15666/aeer/1704_72657281
|View full text |Cite
|
Sign up to set email alerts
|

Compositions of Prokaryote Communites and Their Relationship to Physiochemical Factors in December in Chaohu Lake and Three Urban Rivers in China

Abstract: The aim of this study was to determine the impacts of anthropogenic disturbances on compositions of prokaryote communites (CPCs) in Chaohu Lake and its three urban tributaries, in China. Prokaryotic diversity in Chaohu Lake and its tributaries was high, and prokaryotic communities showed lower richness in Nanfei River than in Zhegao River and Hangbu River, with waterbody nutrient levels negatively corresponding to prokaryotic diversity. Except for a few rare prokaryotes, or where classification was unclear, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Although increment in pH was observed in the present study, the reason caused the increment needs to be further study. Wu et al [34] reported that the correlations between environmental factors and various microbiota in the Chaohu Lake and three urban rivers in China were dissimilar. The results showed that the concentrations of ammonia nitrogen, NO 3 − -N, and NO 2 − -N in the tested aquaculture water were significantly correlated with the microbiota composition (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Although increment in pH was observed in the present study, the reason caused the increment needs to be further study. Wu et al [34] reported that the correlations between environmental factors and various microbiota in the Chaohu Lake and three urban rivers in China were dissimilar. The results showed that the concentrations of ammonia nitrogen, NO 3 − -N, and NO 2 − -N in the tested aquaculture water were significantly correlated with the microbiota composition (Figure 4).…”
Section: Discussionmentioning
confidence: 99%